Multi-threading on Linux Operating System Using Scheduling Algorithm - Rahmad Syuhada (Institute of Computer Science (IOCS), 2021)
The choice of operating system in terms of convenience and operation has become a major priority for users, where the operating system has a systematic scheduling that includes data processing, data storage, calculation of memory usage and other resources. The system is a group of elements or parts that interact with each other, are interrelated, depend on each other, function together as a whole to achieve a goal. The operating system continues to develop until now, so that the operating system is also in the center of attention because of its very fast development. One of the operating systems that has become the center of attention in this development is GNU / Linux. Therefore it is necessary to analyze the multi-threading technique with the Round Robin Algorithm to see the process running simultaneously whether there is concurrency in many processes or execution to calculate the existence of threads in a process.